The Non‐Adult Cohort from Le Morne Cemetery, Mauritius: A Snap Shot of Early Life and Death after Abolition. (25th July 2012) - Appleby, J.; Seetah, T. K.; Calaon, D.; Čaval, S.; Pluskowski, A.; Lafleur, J. F.; Janoo, A.; Teelock, V.
ABSTRACT The cemetery of Le Morne in Mauritius dates from the 1830s and is thought to contain the remains of slaves, freed slaves or potentially free Madagascans, which in itself has economic and social implications and makes the cemetery all the more intriguing. During 2010, excavations recovered the remains of 11 individuals, of which six were children. Although a small sample, the burials of the non‐adults show several interesting features. Two neonates were buried contemporaneously and may have been twins, while a late term foetus in a grave with a young woman may represent an incident of coffin birth. This sample has the potential to cast light on the burial practices of the slave/ex‐slave community in Mauritius, about which little is currently known. Copyright © 2012 John Wiley & Sons, Ltd.